Recent progresses in improving nanowire photodetector performances - Yan, Chaoyi (2013)
Recent advancements of nanowire (NW) photodetector performances are reviewed. This review focuses on the key performance improvements and strategies towards low-cost device fabrication, fast photoresponse time, high wavelength selectivity and high sensitivity, which are among the most important characteristics of NW photodetectors. Representative reports demonstrating significant improvements in the aforementioned device properties are summarized and analysed. NW networks are emerging as promising structures than conventional single NW devices which are facing NW assembly problem and require expensive and intense lithography steps. The network devices are also advantageous in achieving fast photoresponse time due to the fast response rate of junction barriers. High wavelength selectivity in NW photodetectors was achieved with ternary alloyed NWs with tunable bandgaps and hence cut-off wavelengths. Ternary oxides with larger bandgaps than those common binary oxides were found to be superior candidates for selectively deep-UV detection. Sensitivity can be improved by functionalizing the NW channel with polymer or making use of the piezoelectric property of the NWs. The progresses made in improving photodetector performances are expected to greatly accelerate their practical applications. An outlook and future research directions are also presented.